A New Nucleic Acid Prodrug Responsive to High Thiol Concentration: Synthesis of 2′‐O‐Methyldithiomethyl‐Modified Oligonucleotides by Post‐Synthetic Modification. Issue 1 (15th February 2018) - Ochi, Yosuke; Nakagawa, Osamu; Hayashi, Junsuke; Wada, Shun‐ichi; Urata, Hidehito
Abstract: This unit describes the synthesis of 2′‐ O ‐methyldithiomethyluridine‐containing oligonucleotides, which can be deprotected to yield the parental oligoribonucleotides under high concentrations of glutathione similar in cytoplasm. The 2′‐ O ‐methyldithiomethyl group is sensitive to reductive conditions, so that it is incompatible to 3′‐ O ‐phosphoramidite modification in nucleosides. Thus, a novel post‐synthetic approach to obtain 2′‐ O ‐methyldithiomethyluridine‐containing oligonucleotides was developed, in which 2′‐ O ‐(2, 4, 6‐trimethoxybenzylthiomethyl)uridine‐modified oligonucleotides are readily converted by treatment with dimethyl(methylthio)sulfonium tetrafluoroborate to the 2′‐ O ‐methyldithiomethyluridine‐modified oligonucleotides. The 2′‐ O ‐methyldithiomethyluridine‐modified oligonucleotides are readily and cleanly converted to the parental oligonucleotides under high thiol conditions, such as 10 mM glutathione and dithiothreitol. © 2015 by John Wiley & Sons, Inc.